KERANGKA KERJA ANALITIS FORMULASI STRATEGI KOMPREHENSIF PT XYZ PURWAKARTA - Tresna Wulandari; Ningsih Ningsih (Jurnal Teknologika, 2023)
Abstract. Referring to PT XYZ's sales and production quantity data as an indicator of financial and internal process performance, there was an increase in the value of the rupiah from 2019 to 2021, but the number of products sold and production decreased in 2020. Based on customer complaint data, they are a trend of increasing complaints from 2017 to 2021, where the object of the complaint is dominant regarding product quality. Specifically for 2021, customer complaints will fluctuate, and the highest number of complaints will occur in June and November. Regarding the HR perspective, high levels of employee absenteeism and employee turnover have been found. Based on a series of empirical data obtained in 2021, and several problems and challenges therein, it is appropriate for the management of PT XYZ to evaluate the effectiveness of last year's strategy and efforts to review the formulation of the company's strategy regularly, including in 2022. These efforts are needed to anticipate various possible risks from strategy formulation such as subjective information and analysis; personal bias, political aspect, emotion, personality, and halo error.